Pengaruh Permainan Tradisional Boy-boyan Terhadap Perkembangan Motorik Anak di Taman Kanak-kanak Ramah - Lisha Desti Rahayu; Syahrul Ismet (Universitas Negeri Padang, 2021)
This study aims to determine how much influence this boy-boy game has on the motor development of children aged 5-6 years in the Nagari Gurun Panjang Child Friendly Kindergarten, the experimental method in the form of a quashi experimental population of children in the Nagari Gurun Panjang Child Friendly Kindergarten. . The technique of taking samples was purposive sampling in 2 groups, namely the control group (B1) with 10 children and the experimental group (B2) with 10 children. The average achievement of the experimental group children's abilities was higher (score 118) than the control group children (110). While the results of hypothesis testing using the T-test 2.450 2.10092, it can be concluded that there is a significant difference between the motor skills of children in the control group and the experimental group.